1976
DOI: 10.1097/00000658-197605000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects on Gastrin and Gastric Secretion of Five Current Operations for Duodenal Ulcer

Abstract: We have measured serum gastrin and gastric acid secretion in 66 duodenal ulcer patients before and after vagotomy and pyloroplasty (V + P--15 patients), selective proximal vagotomy without drainage (SPV - D--11 patients), and with drainage (SPV + D--19 patients), and vagotomy, antrectomy, and either gastroduodenostomy (V + BI--15 patients) or gastrojejunostomy (V + BII--6 patients). Basal and peak postprandial gastrin levels were increased in postoperative V + P, SPV - D, and SPV + D patients. Basal and peak p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 23 publications
1
7
1
2
Order By: Relevance
“… 62 , 64 , 65 Each of the three acid hyposecretory criteria used in the present study is more than 8‐fold less than the peak secretory values usually seen in a patient after gastric resection without ZES. The mean basal acid secretory rate after a Billroth II or Billroth I operation in patients without ZES in one study was 1.3 ± 1.0 mEq/h and 0.9 ± 0.3 mEq/h, 66 respectively, and in a second study after a partial gastrectomy were 0.83 and 1.9 mEq/h in patients with or without a post‐operative marginal ulcer 67 . These values are also significantly higher than the value of 0.2 mEq/h used as the most stringent criterion of hyposecretion in the present study.…”
Section: Discussionmentioning
confidence: 94%
“… 62 , 64 , 65 Each of the three acid hyposecretory criteria used in the present study is more than 8‐fold less than the peak secretory values usually seen in a patient after gastric resection without ZES. The mean basal acid secretory rate after a Billroth II or Billroth I operation in patients without ZES in one study was 1.3 ± 1.0 mEq/h and 0.9 ± 0.3 mEq/h, 66 respectively, and in a second study after a partial gastrectomy were 0.83 and 1.9 mEq/h in patients with or without a post‐operative marginal ulcer 67 . These values are also significantly higher than the value of 0.2 mEq/h used as the most stringent criterion of hyposecretion in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Proximal gastric vagotomy, as Thompson (1976) and other workers have shown, causes a fall in acid secretion and a rise in the serum gastrin response. The persistence of a significant basal acid secretion which increases with time, as noted by Jordan (1976a), together with the decrease i n the percentage of negative Hollander tests, from around 60% to 80% at one month, and down to 30% at 12 months, causes concern that the recurrence rate of ulcer may increase after proximal gastric vagotomy.…”
Section: The Effect Upon Acid Secretionmentioning
confidence: 76%
“…By contrast, raised-gastrin levels were only a reflection of the increase in basal levels of gastrin, an established effect of truncal vagotomy. [36][37][38] Intragastric titration studies with control of luminal pH have shown that this post-vagotomy hypergastrinaemia cannot be explained entirely by loss of inhibition by endogenous HCI when acid secretion is reduced. 39 The increased cholecystokinin release noted in this study might be needed to achieve the same enzyme output from the pancreas, if reduced acid secretion after highly selective vagotomy diminished pancreatic sensitivity.…”
Section: Discussionmentioning
confidence: 99%